Doveweed (Murdannia nudiflora) Control in Warm-Season Turfgrass Species - Ramon G. Leon; J. Bryan Unruh (EDIS, 2015)
Doveweed is an aggressive, naturalized summer annual weed that rapidly invades warm-season turfgrass species, especially in residential lawns, and few herbicides can effectively control it. Because of these challenges, a well-designed management strategy is necessary for doveweed control. This 4-page fact sheet describes identification, growth requirements, chemical control and cultural practices. Written by Ramon G. Leon and Bryan Unruh, and published by the UF Department of Agronomy, June 2015.